Catch-all Politics of Women Politicians in Organizing Political Parties in Banten Province - Mayrudin, Yeby Ma'asan; Utami, Wahyu Kartiko; Irawan, Peri; Afala, La Ode Machdani (Journal of Governance, 2025)
This article discusses the involvement of female politicians in organizing political parties that open up opportunities for the manifestation of catch-all politics in Banten. Catch-all politics is a strategy of political parties that embraces all parties, especially the women's community, to join and fight together. The research uses descriptive qualitative methods through data collection from informants, literature, and media studies to "discover the nature of the specific events". The results of this study are: First, the dimension of women's political existence is currently progressive and appreciated, not excluded or discredited; Second, political parties in Banten have begun to build catch-all politics for the existence of women politicians based on the need for affirmative action and the functionalization of women politicians as “color” providers in organizing political parties.